A study of the heat insulation performance of pre-oxidized fiber felts of silica aerogel/silicon carbide composite coatings. Issue 9 (2nd September 2019) - Liu, Yuanjun; Liu, Xulin; Li, Jianming; Liang, Tonglong; Zhao, Xiaoming
Abstract: In this article, pre-oxidized fiber felts of silica aerogel/silicon carbide composite coatings were prepared by the coating process and then compounding silica aerogel with silicon carbide powder as the infrared sunscreen on the pre-oxidized fiber felts. The influence of the ratio of the contents of the silica aerogel and silicon carbide as the infrared sunscreen on the heat insulation performance of coating composites of pre-oxidized fiber felts was discussed, and their mechanical properties were investigated. The results show that with increasing silicon carbide content in the composite coating, the coefficient of thermal conductivity increases gradually; when the working temperatures were 100, 150 and 200 °C, the coating composites of pre-oxidized fiber felts had the best heat insulation performance when the mass ratio of the silica aerogel and silicon carbide was 4:7. The working temperature and the steady-state temperature difference of the coating composites shows a linear relationship, so simple calculation methods of the coefficient of thermal conductivity for the coating composites were given at higher temperatures.